Implementation of Peraturan No. 1 Tahun 2015 on Management and Public Information Service in Binjai General KPU - Hanim, Fatimah; Kurniaty, Evi Yunita (Talenta Publisher, 2019)
The problems raised in this study are: (1) Lack of human resources to fill the structure so that concurrent positions occur in the work system in Binjai City KPU, (2) Lack of facilities and infrastructure in Binjai City KPU, (3) Still lack of socialization in Implementation Election Commission Regulation Number 1 of 2015. This study uses qualitative research methods, which are used in a study to obtain a qualitative description and will be dominated by many words, sentences and descriptions and rarely use numerical data, although it does not rule out the possibility of displaying tables or graphs to support the completeness of the data. From the results of the study, it is known that the existence of Regulation of the General Election Commission No. 1 of 2015 has a significant impact on improvements in public services, namely services that are getting better in